Larval rockfish growth and survival in response to anomalous ocean conditions - H. William Fennie; Kirsten Grorud-Colvert; Su Sponaugle (Scientific Reports, 2023)
Abstract Understanding how future ocean conditions will affect populations of marine species is integral to predicting how climate change will impact both ecosystem function and fisheries management. Fish population dynamics are driven by variable survival of the early life stages, which are highly sensitive to environmental conditions. As global warming generates extreme ocean conditions (i.e., marine heatwaves) we can gain insight into how larval fish growth and mortality will change in warmer conditions. The California Current Large Marine Ecosystem experienced anomalous ocean warming from 2014 to 2016, creating novel conditions. We examined the otolith microstructure of juveniles of the economically and ecologically important black rockfish (Sebastes melanops) collected from 2013 to 2019 to quantify the implications of changing ocean conditions on early growth and survival. Our results demonstrated that fish growth and development were positively related to temperature, but survival to settlement was not directly related to ocean conditions. Instead, settlement had a dome-shaped relationship with growth, suggesting an optimal growth window. Our results demonstrated that the dramatic change in water temperature caused by such extreme warm water anomalies increased black rockfish growth in the larval stage; however, without sufficient prey or with high predator abundance these extreme conditions contributed to reduced survival.